2011
DOI: 10.1007/s00468-011-0540-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate controls act at different scales on the seasonal pattern of Quercus ilex L. stem radial increments in NE Spain

Abstract: Long-term data on radial increment dynamics in Mediterranean species may identify which climatic variables are the main constraints for radial growth and at which temporal scales they act. To this end, we examined stem radial fluctuations in Quercus ilex L., the dominant evergreen oak species in the Western Mediterranean Basin, over a period of 11 years (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) at a coastal site in north-eastern Spain. We used manual band dendrometers to record girth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 39 publications
(51 reference statements)
9
59
0
Order By: Relevance
“…However, the Portuguese oak shows an earlier phenological development (most primary and secondary growth occur in spring) than holm oak which is able to grow during summer (MontserratMartí et al 2009;Albuixech et al 2012). This is also reflected in the radial growth responses to climate, since tree ring width usually increases in response to wet spring or summer conditions in the case of Portuguese and holm oaks, respectively (Corcuera et al 2004a(Corcuera et al , 2004bGutiérrez et al 2011). From an ecophysiological point of view, the holm oak is a droughttolerant species displaying a tight stomatal control over transpiration, while Mediterranean oak species similar to Portuguese oak show a higher conductance but also experience xylem embolism due to summer drought and freezethaw events in winter (Tognetti et al 1998).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, the Portuguese oak shows an earlier phenological development (most primary and secondary growth occur in spring) than holm oak which is able to grow during summer (MontserratMartí et al 2009;Albuixech et al 2012). This is also reflected in the radial growth responses to climate, since tree ring width usually increases in response to wet spring or summer conditions in the case of Portuguese and holm oaks, respectively (Corcuera et al 2004a(Corcuera et al , 2004bGutiérrez et al 2011). From an ecophysiological point of view, the holm oak is a droughttolerant species displaying a tight stomatal control over transpiration, while Mediterranean oak species similar to Portuguese oak show a higher conductance but also experience xylem embolism due to summer drought and freezethaw events in winter (Tognetti et al 1998).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Thus, diverse growth responses to droughts of different duration and intensity are expected from regional to local scales depending on the climatic conditions of each site and the responsiveness of each tree species (Gutiérrez et al, 2011;Pasho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gutierrez et al (2011) reported that Quercus ilex L. radial increment was mainly constrained by temperature, whereas Camarero et al (2010) observed that in Juniperus thurifera L. and Pinus halepensis (Miller) the climatic response changed during the year, with stem radius variations dependent on temperature during growth onset and on precipitation during the summer. A different study revealed that Abies pinsapo (Boiss.)…”
Section: Introductionmentioning
confidence: 99%